Paeonol Induces Protective Autophagy in Retinal Photoreceptor Cells - Zhang, Daowei; Wu, Jiawen; Wu, Jihong; Zhang, Shenghai (Frontiers in Pharmacology, 2021)
Retinal photoreceptor (RP) cells are widely involved in retina-related diseases, and oxidative stress plays a critical role in retinal secondary damage. Herein, we investigated the effectiveness and potential mechanisms of autophagy of paeonol (Pae) in terms of oxidation resistance. The animal model was induced by light damage (LD) in vivo, whereas the in vitro model was established by H2O2 stimulation. The effectiveness of Pae was evaluated by hematoxylin and eosin(HE), terminal deoxynucleotidyl transferase dUTP nick end labeling(TUNEL) assay, immunofluorescence, transmission electron microscopy, electroretinogram (ERG), and Western blot analysis in vivo, and the underlying mechanisms of Pae were assessed by Cell Counting Kit-8(CCK-8) assay, reactive oxygen species (ROS) assay, and Western blot analysis in 661W cells. We mainly evaluated the effects of Pae on apoptosis and mitophagy. The LD-induced increased apoptosis and decreased mitophagy of RPs were mitigated by Pae treatment. The decreased cell viability and mitophagy induced by oxidative stress in 661W cells were reversed by Pae, which increased the expression of mitochondrial functional protein cytochrome c. Experiments showed that mitophagy was downregulated in non-hypoxia-induced and hypoxia-induced pathways under H2O2 stimulation and was upregulated by Pae treatment. Pae increased the cell viability and reduced ROS levels through mitophagy. Pretreatment with Pae preserved RP cells by enhancing mitophagy, which protected retinal function.